Pemanfaatan Tepung Ampas Tahu dengan Penambahan Pasta Kacang Merah dalam Formulasi Snackbar - Putri Septya Ningrum Chaniago; Suko Priyono; Nur Endah Saputri (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
Snack bar is a food product made from a combination of ingredients that are bound together by a binding agent. One type of snack bar is a protein bar. A potential primary ingredient for making high-protein snack bars is tofu dregs. "The protein content in tofu dregs is relatively high about 26.6% and has not been optimally utilized and often becomes waste and pollutes the environment. The production of snack bars can incorporate various ingredients, one of which is red beans. Red beans are a source of plant-based protein, containing about 11% protein. This research aims to develop a snack bar with the best formulation of red bean paste and tofu dregs flour in terms of sensory and chemical characteristics. The research was conducted using a Randomized Block Design with one factor, that is the formulation with five ratio comparisons of tofu dregs flour to red bean paste: r1 (90:10), r2 (80:20), r3 (70:30), r4 (60:40), and r5 (50:50), each with five repetitions. The results revealed that the snack bar with a tofu dregs flour to red bean paste ratio of 60:40 was the best treatment, with physicochemical characteristics of 19.34% moisture content, 1.98% ash content, and 6.81% protein content as well as sensory characteristics including aroma 3.8 (liked), taste 4.17 (more liked), texture 3.9 (liked), and color 3.73 (liked).